DarkWeb Crawling using Focused and Classified Algorithm - Yunelfi, Putri Rahmasari; Purwanto, Yudha; Ruriawan, Muhammad Faris; Popalia, Agus Setiawan; Fahrani, Fina (Universitas Telkom, 2022)
At this moment there are more and more cases of illegal goods transactions and personal data being leaked. Illegal transactions and personal sales data are usually carried out on the deep web, especially dark web because the web has multiple layers of encryption and an anonymous system when accessing it. without any illegal transactions and personal sales data, basically the web is very wide and deep. Therefore, the crawling method can be used to explore the dark web. The crawling method on the dark web can use a crawl focus that takes a focused approach on a particular topic. The focus crawling method takes a URL approach by looking at URL that are interconnected with the main URL page on the desired topic. To do focus crawling, it is done by entering keywords that best match the desired topic. With the focus crawling method, it is hoped that the maximum URL data set related to a particular topic can be generated. From the results obtained on the crawling system on the dark web, it is hoped that it can also be used to find out the number of URLs related to certain topics. In addition, the results of this crawl can also be a source of information for further research on the dark web.